Effectiveness of Compensation on Teacher Professionalism and Performance - Nuryanti, Nuryanti; Ida Rindaningsih (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This paper discusses how compensation affects teacher professionalism and performance. Teachers play a major role in an educational institution. As an educator, his main task is to educate students and interact directly to produce a generation that has superior character so that it can face the challenges of the times. An educator in carrying out these tasks should get proper compensation considering the duties and obligations he carries out so much. On the basis of the description above, the author conducted research with the title of the effectiveness of compensation on professionalism and teacher. This study aims to examine and analyze the extent to which compensation can affect teacher professionalism and performance. The method used in this research is literature review. Data collection is obtained through problem formulation, collecting 15 articles that are in accordance with the topic, conducting a comparative study of the research results, presenting data and making. From here the results obtained that the amount of compensation greatly influences the professionalism and performance of teachers.